Contemplative Transformations: A Blueprint for Creating Culture of Care Learning Environments - Sortino, Robert Dion (Journal of Organizational Psychology, 2018)
A qualitative data research approach was used to collect data using the phenomenological research method in an attempt to illuminate the voices of leaders indicating that spirituality was an underpinning influencing their decision-making to create positive school culture. In-depth, semi-structured interviews of six administrators from different ethnic backgrounds and diverse educational programs were conducted. An analysis of the data revealed a rich and thick description of how the six participants relied on contemplative practices to find wisdom and guidance to make sound moral and ethical decisions to create nurturing learning environments at their schools by improving school climate and culture.